2007
DOI: 10.1149/1.2789301
|View full text |Cite
|
Sign up to set email alerts
|

Area-Selective Atomic Layer Deposition of Platinum on YSZ Substrates Using Microcontact Printed SAMs

Abstract: Using ͑methylcyclopentadienyl͒trimethylplatinum ͑MeCpPtMe 3 ͒ and oxygen as precursors, Pt has been deposited by atomic layer deposition ͑ALD͒ on the surfaces of yttria-stabilized zirconia ͑YSZ͒, a solid oxide electrolyte, as well as on oxide-covered silicon. Ex situ analyses have been carried out to examine the properties of both as-deposited and postannealed Pt films. X-ray photoelectron spectroscopy measurements demonstrate that there are no detectable impurities in the as-deposited Pt films, and four-point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
127
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(133 citation statements)
references
References 47 publications
6
127
0
Order By: Relevance
“…Pt growth on these substrates could only be achieved by using a higher O 2 pressure ͑Ͼ0.8 mbar͒ as also typically used in the literature. 1,3 On the contrary, remote plasma ALD of Pt ͑0.5 s O 2 plasma͒ leads to immediate growth without a substantial nucleation delay. From the ellipsometry measurements, which have a reduced accuracy in the first 1-2 nm, it is concluded that growth per cycle is constant after the first 50 cycles.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pt growth on these substrates could only be achieved by using a higher O 2 pressure ͑Ͼ0.8 mbar͒ as also typically used in the literature. 1,3 On the contrary, remote plasma ALD of Pt ͑0.5 s O 2 plasma͒ leads to immediate growth without a substantial nucleation delay. From the ellipsometry measurements, which have a reduced accuracy in the first 1-2 nm, it is concluded that growth per cycle is constant after the first 50 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…8 Material properties.-As shown in Table I both the remote plasma and thermal ALD process result in very similar material properties for the Pt films. In both cases high density ͑ϳ21 g/cm 3 ͒, low resistivity ͑ϳ15 ⍀ cm͒, and high purity Pt films were deposited. The density and resistivity for these ϳ30 nm thick films are close to the bulk values of 21.4 g/cm 3 and 10.8 ⍀ cm, and they are similar to the values reported for thermal ALD of Pt.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations